Prevalence and knowledge of urinary incontinence and possibilities of treatment among low-income working women - Amabily Carolline Zago; Maria Angelica Saquete Fambrini; Elaine Priscila Garcia Silva; Alberto De Vitta; Marta Helena Souza De Conti; Gabriela Marini
Abstract Introduction: Urinary incontinence (UI) can affect women's lives in all areas, including in the occupational context, due to an uncomfortable workplace, incorrect positions for long periods of time and the handling of heavy items. Another worrying aspect is that the knowledge about urinary incontinence, in the health area, and its forms of treatment is still small among the low-income population. Objective: To verify the prevalence and knowledge about urinary incontinence and treatment possibilities among low-income working women. Methods: A cross-sectional study carried out on working women of a poultry processing plant. Results: The study included 136 women with an average age of 33.7 ± 9.7 years; body mass index of 26.6 ± 5.6 kg/m2; parity of 2.1 ± 1.1 children; monthly income of 2.3 ± 1 minimum wages. Of those interviewed, 63.9% were white; 44.8% had incomplete primary education; 52.9% were single; 53.6% underwent cesarean section delivery; and of those who underwent normal labor delivery, 86.6% underwent episiotomy. The prevalence of urinary incontinence was found to be 2.9%, and among the women affected, two reported that UI led to sexual, social, water and occupational restriction, and one of them believes that UI interferes with her concentration and productivity in the workplace. Regarding health knowledge, 46.3% had never heard of urinary incontinence before, and more than half (66.1%) did not know about the existence of medical treatment. All women interviewed (100%) were unaware of the existence of physiotherapeutic treatment. Conclusion: The prevalence of urinary incontinence was among those interviewed was small, however, the knowledge about the symptoms and possibilities of medical, and mainly physiotherapeutic treatment. is scarce among these women. This study allows to alert and to guide the health professionals and the society about the importance of actions that promote health education in the low income population, besides allowing these women to prevent or seek the appropriate treatment in order to guarantee a better quality of life.